Studying the Extraction Conditions on Rosmarinic Acid Content and Antioxidant Activity of Basil (Ocimum basilicum L.) - Pham, Anh Giang Que; Pham, Tram Thi My (Universitas Gadjah Mada, 2025)
Basil (Ocimum basilicum L.), a popular herbal plant, is known for its ornamental and therapeutic importance. It has been described as having antioxidant, anti-inflammatory, hepatoprotective, immunomodulatory, antihyperglycemic, and antimicrobial properties. This study aimed to evaluate the effects of some factors on the rosmarinic acid concentration and antioxidant activity of basil extract, such as samples, solvents (water and 50% ethanol), solvent-to-sample ratios (from 1:20 to 1:70 g/mL), extraction temperature (70, 90, and 110 °C), and extraction time (30, 60, 90, and 120 min). Rosmarinic acid content was analyzed using the spectrophotometry method. The DPPH free radical scavenging experiment was also used to assess the extracts' antioxidant potential. The results showed that with the dried leaves, the ratio between the sample and 50% ethanol was 1:40 g/mL, extraction temperature of 90 °C, and extraction time of 60 min were the best conditions for obtaining rosmarinic acid from basil. The quantitative result also showed that basil extracts had a lot of polyphenols (dark green precipitate) and flavonoids (yellow precipitate). In addition, basil leaves had antioxidant properties with an IC50 value of 3103.18 μg/mL. These findings showed that basil extract may be an important source of antioxidant compounds, such as rosmarinic acid.